Advanced Li-Rich Cathode Collaborated with Graphite/Silicon Anode for High Performance Li-Ion Batteries in Half and Full Cells. (10th November 2015) - Huang, Yanling; Hou, Xianhua; Fan, Xiaoying; Ma, Shaomeng; Hu, Shejun; Lam, Kwok-ho
Graphical abstract: Abstract: A high performance surface modified Li1.2 Mn0.534 Ni0.133 Co0.133 O2 cathode with graphene and CNTs (GNL-modified LMNCO) has been synthesized via a simple ultrasonic dispersion approach. Its morphology and electrochemical performance are investigated thoroughly in this work. Typically, the GNL-modified LMNCO demonstrates an initial discharge capacity of 285.8 mAh g −1, showing initial coulombic efficiency of 83.3%. In addition, impressive discharge capacity of 162.3 and 123.5 mAh g −1 are obtained at 5 and 10 C, respectively. More satisfactorily, it reveals high capacity retention of 217.9 mAh g −1 even after the 180th cycle. The extraordinary electrochemical performance of the GNL-modified LMNCO can be ascribed to the unique conducting network of graphene and CNTs coating on the particles, which greatly improves the conductivity of the electrode and enhances the diffusion coefficient of the Li + . Most significantly, a high-voltage and high-power electrochemical energy storage devices of lithium-ion battery (LIB) full cell has been simultaneously assembled with the GNL-modified LMNCO as cathode and silicon/graphite/amorphous carbon (Si/C) composite as anode, whose properties outclass many other systems of LIB full cells. Therefore, the acquaintance of the compatibility of the Li-rich cathode and Si/C composite anode for high-voltage and high-energy LIB full cells should attract more research efforts in the future.